Signal qualities, order of decisions, and informational cascades: Experimental evidences - Shunichiro Sasaki (Osaka University, Institute of Social and Economic Research (ISER), 2004)
This paper reports the results of informational cascades experiments where two different decision-making systems, anti-seniority and seniority are investigated. By implementing heterogeneous signal qualities associated with the fixed order of decisions I compare the property of each system and examine heuristics human subjects use. Major findings are the following: (1) complete cascades occur more frequently in seniority than in anti-seniority, (2) seniority is more e'cient than anti-seniority, but it increases the risk for creating negative cascades, (3) for both systems, rational complete cascades occur less frequently than those which the Bayesian theory predicts, (4) subjects in seniority put equal weight on private signals and on predecessors' predictions whereas those who in anti-seniority put more weight on private signals than on predecessors' predictions, (5) by analyzing deviations from Bayesian posteriors, both overconfidence and underconfidence are identified, and (6) the anchoring effect is vericed in deviations by overconfidence, but is not verified in deviations by underconfidence.
Keywords: C91; C92; D81; 330; informational cascades; experiment; signal quality; overcondence; undercondence; Signalling; Vertrauen; Entscheidungstheorie; Herdenverhalten